Development of regional economies: theoretical approaches and management strategy (Economics and region, 2025)
The article analyzes in detail the current challenges and key trends in regional development in Ukraine, in particular in the context of the decentralization reform and the consequences of military operations that significantly affect the socio-economic situation in the country. Particular attention is paid to the aspects of fiscal decentralization, which gives local authorities much greater opportunities to formulate and implement economic development strategies at the regional level. The importance of integrating national and local development strategies in order to achieve sustainable economic recovery, in particular in post-conflict areas, is determined. Theoretical and methodological approaches to defining the essence of the “regional economy” are revealed, focusing on the territorial approach, which allows to adequately assess economic processes within individual regions, taking into account their socio-economic, cultural and infrastructural characteristics. In addition, it considers the principles and tools of strategic management of regional development, including mechanisms of financial regulation, development of cluster initiatives and investment programs that promote economic growth at the local level. Attention is focused on the need to adapt development strategies to the specific conditions of post-war recovery, which require a special approach to the restoration of infrastructure, enterprises, as well as social and cultural revival. It is determined that for the effective restoration of the territories, it is necessary to integrate resources at the national and international levels, which will provide the necessary funding and technologies for adaptation and modernization of the affected regions, as well as increase their competitiveness in the long term. It is determined that in order to ensure the sustainability of regional development, it is important to take into account the specifics of each region, developing its unique resources and potential, which will contribute not only to the recovery but also to sustainable economic growth in the context of global changes.
Keywords: region; regional economy; regionalism; theoretical base of regionalism; methodological positions of regionalism; regional development factors; regional development management strategy; strategic planning; resource constraints; regional potential; types of regional development